2010
DOI: 10.1111/j.1600-0714.2009.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐expression of Hif1α and CAIX is associated with poor prognosis in oral squamous cell carcinoma patients

Abstract: A co-detection of low Hif1alpha/CAIX expression is significantly correlated with a better prognosis for OSCC patients, which may have implications for therapy options for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…HIF1α regulates genes involved in tumor initiation, progression, and metastasis (55), and HIF1α overexpression correlates with a poor prognosis in human head and neck cancer (56). We show that RARγ and RXR agonists inhibit the HIF1α signaling pathway in the context of tongue carcinogenesis (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…HIF1α regulates genes involved in tumor initiation, progression, and metastasis (55), and HIF1α overexpression correlates with a poor prognosis in human head and neck cancer (56). We show that RARγ and RXR agonists inhibit the HIF1α signaling pathway in the context of tongue carcinogenesis (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…24 Because of these difficulties, additional independent prognostic markers need to be identified to improve the diagnosis and therapeutic regimens. 6,7 It has been suggested that hypoxia is an independent adverse prognostic factor in patients with head and neck cancer. 25 The main transcription factor activated by hypoxia is HIF-1a, which regulates cell metabolism as part of the cell's response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The largest functional group of genes consistently regulated by HIF-1a are the genes associated with glucose metabolism. 6 HIF-1a increases the rate of glucose uptake through the transcriptional activation of the facultative glucose transporters GLUT-1 and GLUT-3. Elevated expression of either HIF1-a or GLUT-1 has been detected in many different cancers, including head and neck tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cox proportional hazards model was applied to identify prognostic variables that predict overall survival and disease-free survival. The power calculation was done with PASS (V. 08.0.3, NCSS), assuming the 5-year survival rate to be 50% (27), hazard ratio to vary from 2.17 to 4.53 (21,(28)(29)(30), the proportion in control group 1 to be 47.5% (HIF-1α negative) or 39.2% (HIF-2α negative), and twoside α as 0.05. The log-rank test with an overall sample size of 97 subjects achieved 81.72% to 99.94% power for HIF-1α and 76.69% to 99.74% power for HIF-2α.…”
Section: Statisticsmentioning
confidence: 99%